Association of Immune Related Adverse Events With Efficacy of Immune Checkpoint Inhibitors and Overall Survival in Cancers: A Systemic Review and Meta-analysis - Fan, Yong; Xie, Wenhui; Huang, Hong; Wang, Yunxia; Li, Guangtao; Geng, Yan; Hao, Yanjie; Zhang, Zhuoli (Frontiers in Oncology, 2021)
Objectives: Immune checkpoint inhibitors (ICIs) have brought impressive benefits to cancer patients, however often with immune-related adverse events (irAEs). We aimed to investigate the association of irAEs with efficacy and overall survival in cancer patients treated by ICIs, and further quantify the association by stratifying subgroups. Methods: PubMed, EMBASE and Cochrane library from database inception to 29 August 2019 were systematically searched. Articles reporting association of objective response rate (ORR), progression-free survival (PFS), overall survival (OS) with irAEs in cancer patients treated with approved ICIs were included. Adjusted odds ratios (OR) with 95% confidential intervals (CIs) were calculated for ORR, and hazard ratios (HR) were used for PFS and OS. Results: A total of 52 articles comprising 9156 patients were included. Pooled data demonstrated a statistically significant greater probability of achieving objective tumor response for patients with irAEs compared those without (OR 3.91, 95% CI 3.05-5.02). In overall meta-analysis, patients who developed irAEs presented a prolonged PFS (HR 0.54; 95% CI 0.46-0.62) and OS (HR 0.51; 95% CI 0.41–0.59). More specifically, irAEs in certain cancer types (NSCLC and melanoma) and organs (skin and endocrine) were robustly associated with better clinical outcomes, while it need to be further verified in other situations. High grade toxicities (G3-5) were not associated with a significantly favorable PFS or OS. Additionally, the association between irAEs and clinical benefit seemed to be more definite in patients receiving PD-(L)1 blockade than CTLA-4 blockade. Pooled data from landmark analyses displayed a consistent result. Conclusions: The occurrence of irAEs predicted improved tumor response and better survival in overall cancer patients treated with ICIs. Notably, the association stayed robust in certain cancer types (NSCLC and melanoma) and organs-specific irAEs (skin and endocrine).